Development of frozen buko pie - Villegas, Christine Alvarado
The research was conducted to develop a frozen buko pie intended for export and local distribution. The study was divided in three phases. The first phase was further divided into three subphases which all aimed to develop and standardize the formulation of the buko pie filling. The following results were obtained: (a)6% as the optimum level of incorporation of pregelatinized starch, (b) no addition of egg to the filling to lessen its richness, and (c)11% sugar and 1.5% butter as the optimum combination for the pie filling. In phase II, the best condition of the crust prior to freezing and the optimum freezing temperature for the buko pie were studied. Although this phase was divided into two parts, the study was done simultaneously. Through the Analysis of Variance, it was established that the buko pie be frozen unbaked and stored at or lower than -17°C. Phase III dealt with the study on the storage stability of the buko pie for three months at the predetermined freezing condition. It involved three tests to which the pies were subjected. These were the microbiological test, chemical test, physico-chemical test and sensory evaluation. The result of the microbiological test indicated a decreasing microbial count of the product during the three month storage. The pH and Aw readings for three months showed an increasing trend while the SS readings remained constant. The sensory attributes of the buko pie after three months of storage were: moderately soft texture for the fillings, tender and crusty texture for the crust, light yellow color, no starchy taste, distinct buko flavor, and just right degree of sweetness. At the end of 3 months of storage, 50% of the panelists liked the product very much while 33% liked it extremely and 17% liked it moderately.